PENGARUH STRUKTUR KEPEMILIKAN, KEPUTUSAN PENDANAAN, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Muvidha, Nurul Isvatul; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out an empirical evidence about some factors which influence firm valueon LQ-45 companies which are listed in Indonesia Stock Exchange. Some factors which have been tested in theresearch i.e. institutional ownership, managerial ownership, funding decisions, profitability and firm size.Thesamples are 80 LQ-45 companies which are consistently listed in Indonesia Stock Exchange in 2011-2014periods which have been selected by using purposive sampling method. These factors are tested by busingmultiple regressions analysis at significance level 5 percents by using statistic test instrument the SPSS(Statistical Product and Service Solutions) 20th version. The result of the analysis show that institutionalownership has positive influence to the firm value, with the significance value 0,000 is smaller than Î±= 0,05 andthe regressions coefficient is 3,994. Funding decisions has positive influence to the firm value, with thesignificance value 0,000 is smaller than Î±= 0,05 and the regressions coefficient is 7,272. Profitability has positiveinfluence to the firm value, with the significance value 0,000 is smaller than Î±= 0,05 and the regressionscoefficient is 10,603. And firm size has positive influence to the firm value, with the significance value 0,000 issmaller than Î± = 0,05 and the regressions coefficient is 4,045. Whereas managerial ownership give no significantinfluence to the firm value, with the significance value 0,938 is greater than Î±= 0,05 and the regressionscoefficient is 0,078.Keywords: Firm value, ownership structure, decisions funding. Profitability, firm size.